Functionally conserved noncoding regulators of cardiomyocyte proliferation and regeneration in mouse and human - Adamowicz,M; Morgan,CC; Haubner,BJ; Noseda,M; Collins,MJ; Paiva,MA; Srivastava,PK; Gellert,P; Razzaghi,B; O'Gara,P; Raina,P; Game,L; et al. (Circulation: Cardiovascular Genetics, 2018)
Background: The adult mammalian heart has little regenerative capacity after myocardial infarction (MI), whereas neonatal mouse heart regenerates without scarring or dysfunction. However, the underlying pathways are poorly defined. We sought to derive insights into the pathways regulating neonatal development of the mouse heart and cardiac regeneration post-MI.Methods and Results: Total RNA-seq of mouse heart through the first 10 days of postnatal life (referred to as P3, P5, P10) revealed a previously unobserved transition in microRNA (miRNA) expression between P3 and P5 associated specifically with altered expression of protein-coding genes on the focal adhesion pathway and cessation of cardiomyocyte cell division. We found profound changes in the coding and noncoding transcriptome after neonatal MI, with evidence of essentially complete healing by P10. Over two-thirds of each of the messenger RNAs, long noncoding RNAs, and miRNAs that were differentially expressed in the post-MI heart were differentially expressed during normal postnatal development, suggesting a common regulatory pathway for normal cardiac development and post-MI cardiac regeneration. We selected exemplars of miRNAs implicated in our data set as regulators of cardiomyocyte proliferation. Several of these showed evidence of a functional influence on mouse cardiomyocyte cell division. In addition, a subset of these miRNAs, miR-144-3p, miR-195a-5p, miR-451a, and miR-6240 showed evidence of functional conservation in human cardiomyocytes.Conclusions: The sets of messenger RNAs, miRNAs, and long noncoding RNAs that we report here merit further investigation as gatekeepers of cell division in the postnatal heart and as targets for extension of the period of cardiac regeneration beyond the neonatal period.